Utility of Gallium‐68 DOTANOC PET/CT in the localization of Tumour‐induced osteomalacia. (15th June 2015) - Bhavani, Nisha; Reena Asirvatham, Adlyne; Kallur, Kumar; Menon, Arun S.; Pavithran, Praveen V.; Nair, Vasantha; Vasukutty, Jayakumar R.; Menon, Usha; Kumar, Harish
Summary: Background: Tumour‐induced osteomalacia (TIO) is a rare disorder characterized by hypophosphataemic osteomalacia caused by small mesenchymal tumours secreting fibroblast growth factor 23 (FGF 23). The most difficult part in the management of these patients is the localization of tumours causing TIO. Objective: We describe the utility of Gallium (Ga)‐68 DOTANOC PET/CT in the localization of tumours causing TIO. Patients and Methods: The study was conducted in a single tertiary referral university teaching hospital in India. Ten patients with TIO who underwent Ga‐68 DOTANOC PET/CT from the time period 2009 to 2014 were included in this study. Their detailed clinical history, biochemical parameters, imaging modalities, surgical interventions, histopathology and outcomes were reviewed. Results: Ga‐68 DOTANOC PET/CT could correctly localize the tumours in TIO in 9 of the 10 cases in which it was performed. Complete resection of the tumour led to full clinical recovery in six of the ten patients; two patients who had partial resection and one patient who underwent radiofrequency ablation showed partial remission. One patient in whom Ga‐68 DOTANOC PET/CT was positive in vertebral body with a low standardized uptake value (SUV) did not show up the tumour on surgery. Conclusions: We conclude that Ga‐68 DOTANOC PET/CT can be used as the first imaging modality in patients diagnosed with TIO. The extremely good outcome following the resection of these small otherwise undiagnosed tumours far outweighs its cost even in resource limited settings.